2009
DOI: 10.1016/j.bbalip.2009.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Oleate β-oxidation in yeast involves thioesterase but not Yor180c protein that is not a dienoyl-CoA isomerase

Abstract: The β-oxidation of oleic acid in Saccharomyces cerevisiae (S. cerevisiae) was studied by comparing the growth of wild-type cells on oleic acid or palmitic acid with the growth of mutants that either had a deletion in the YOR180c (DCI1) gene reported to encode Δ3,5, Δ2,4-dienoyl-CoA isomerase (dienoyl-CoA isomerase) or in the PTE1 gene encoding peroxisomal thioesterase 1. Growth of wild-type cells was indistinguishable from that of YOR180c mutant cells on either palmitic acid or oleic acid, whereas the PTE1 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…In higher eukaryotes, there are two mechanisms by which fatty acids can exit the peroxisome: a carnitine‐dependent route and a thioesterase‐dependent route . In yeast, evidence of involvement of PTE1, the peroxisomal acyl‐CoA thioesterase, in transferring acyl moieties out of peroxisomes was recently reported . Hence, the DHA β‐oxidation intermediates could be transported out of peroxisomes through either carnitine acetyltransferase (Cat2p), or the thioesterase (PTE1) dependent route, or both.…”
Section: Discussionmentioning
confidence: 99%
“…In higher eukaryotes, there are two mechanisms by which fatty acids can exit the peroxisome: a carnitine‐dependent route and a thioesterase‐dependent route . In yeast, evidence of involvement of PTE1, the peroxisomal acyl‐CoA thioesterase, in transferring acyl moieties out of peroxisomes was recently reported . Hence, the DHA β‐oxidation intermediates could be transported out of peroxisomes through either carnitine acetyltransferase (Cat2p), or the thioesterase (PTE1) dependent route, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Gurvitz et al (1999) proposed that 3,5- cis -tetradecadienoyl-CoA is oxidized by the reductase-dependent pathway and involves the dienoyl isomerase Dci1. However, recent data also indicate that the thioesterase-dependent pathway, which involves the acyl-CoA thioesterase Tes1, is operative in S. cerevisiae (Ntamack et al 2009). …”
Section: Peroxisomesmentioning
confidence: 99%
“…It has been suggested that acetate, generated from peroxisomal acetyl-CoA by thioesterases, might be able to exit the peroxisome (24,58). A number of predicted thioesterases occur in C. albicans and in A. nidulans while in S. cerevisiae a single peroxisomal enzyme (Tes1) is regulated by fatty acid induction, and deletion of TES1 results in slightly reduced growth on oleate (41). Alternatively, acetyl-CoA hydrolase could generate acetate (58).…”
Section: Vol 10 2011 Acetyl-carnitine Shuttle In Aspergillus Nidulamentioning
confidence: 99%